Nanoscale glucan polymer network causes pathogen resistance - Eggert, Dennis (Nature Publishing Group, 2014)
Successful defence of plants against colonisation by fungal pathogens depends on the ability to prevent initial penetration of the plant cell wall. Here we report that the pathogen-induced (1,3)-β-glucan cell wall polymer callose, which is deposited at sites of attempted penetration, directly interacts with the most prominent cell wall polymer, the (1,4)-β-glucan cellulose, to form a three-dimensional network at sites of attempted fungal penetration. Localisation microscopy, a super-resolution microscopy technique based on the precise localisation of single fluorescent molecules, facilitated discrimination between single polymer fibrils in this network. Overexpression of the pathogen-induced callose synthase PMR4 in the model plant Arabidopsis thaliana not only enlarged focal callose deposition and polymer network formation but also resulted in the exposition of a callose layer on the surface of the pre-existing cellulosic cell wall facing the invading pathogen. The importance of this previously unknown polymeric defence network is to prevent cell wall hydrolysis and penetration by the fungus. We anticipate our study to promote nanoscale analysis of plant-microbe interactions with a special focus on polymer rearrangements in and at the cell wall. Moreover, the general applicability of localisation microscopy in visualising polymers beyond plant research will help elucidate their biological function in complex networks.